Correlation analysis of FABP3, MCP-4, and CXCL9 levels and myocardial damage in patients with severe pneumonia: FABP3, MCP-4, and CXCL9 levels in myocardial damage of severe pneumonia - Du, Longxia; Wang, Jianping; Wu, Zongxian; Lai, Xianxin; Qian, Xuanchen (Journal of Medical Biochemistry, 2025)
[Objective] To explore the correlations between the levels of serum monocyte chemoattractant protein-4 (MCP-4), heart-type fatty acid binding protein (FABP3), and chemokine ligand 9 (CXCL9) and myocardial damage in severe Mycoplasma pneumoniae (SMPP) patients. [Methods] A total of 158 patients with severe Mycoplasma pneumoniae complicated with myocardial damage were included in the SMPP group. They were divided into a myocardial damage group (n=42) and a nonmyocardial damage group (n=116) according to whether myocardial damage occurred. The control group consisted of an additional 102 healthy people who were examined throughout the same time period. The levels of serum MCP-4, FABP3 and CXCL9 in the two groups were compared. The general clinical data of the patients were recorded. Multivariate logistic analysis was conducted to analyze the risk factors for myocardial damage in patients with severe mycoplasma complicated with pneumonia.[Results] The levels of serum MCP-4, FABP3 and CXCL9 in the SMPP group were significantly greater (all P
Keywords: Severe Mycoplasma pneumoniae; Myocardial damage; Monocyte chemoattractant protein-4; Heart-type fatty acid binding protein; Chemokine ligand 9; Correlation analysis